Analysis and Mitigation of Strategic Risk Business Process by Considering Relationship between Risks: Case Study in Electricity Generation Companies - Lalu Bramantias Gutama; I Nyoman Pujawan (Jurnal Sosial Humaniora, 2019)
This study analyzes the linkages between the causes of strategic risks ofbusiness processes which refer to the balance scorecard perspective incompany X, one ofelectricity generation company. Prioritized 87 risk causeswere identified at the outset using the House of Risk 1 method and thePareto principle so that 17 dominant risk causes were obtained, which werethen analyzed using the ISM method and then weighted using the analyticnetwork process (ANP) method to obtain the new ARP value causes riskthat had accommodated the relationship between the causes of risk. To makeit easier for companies to prioritize the handling of the 17 risk-causingagents, a mitigation analysis was then carried out using the House of Risk2 by considering the ranking of existing effectiveness to difficulty so that 8effective strategies for handling agents causing risk were chosen.